ANALYSIS MOMENT INERTIA OF TIPPE TOP IN FLAT FIELD AS CONTRIBUTION TO MECHANICAL STUDIES - Melly Ariska (Sriwijaya University Learning and Education International Conference, 2018)
The moment of inertia of a reverse gas can be calculated by physically analyzing the parts of the return gas. The back casing consists of a cut ball and a small tube. The back of the head is a ball (sphere) which has a radius R while the handle forms a finger that has fingers. The moment of inertia back gasing is the sum of the moment of truncated inertia and the moment of inertia of the tube with the rotating axis at the center of the mass in the back gas. Backfill is an example of a rigid body system that has a holonomic style, which can move in translation and rotation.